Malignant mixed germ cell tumor of ovary: a rare case report - Tiwary, Bhawana; Sinha, Hemali Heidi; Pandey, Vivek K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Ovarian germ cell tumors are very rare and affect mainly young girls and women. One of the most remarkable advances in oncology is in the treatment of malignant ovarian germ cell tumors. The two histological groups are: dysgerminomas and non dysgerminomatous tumors. We report a case of a 29 years old multiparous woman who presented with persistent pain abdomen and was diagnosed to have a malignant mixed germ cell tumor comprising of both dysgerminoma and yolk sac tumor (endodermal sinus tumor).